PENGARUH LOAN TO DEPOSIT RATIO, CAPITAL ADEQUANCY, NON PERFORMING LOAN, NET PROFIT MARGIN TERHADAP PENYALURAN KREDIT PERBANKAN PADA PT. BANK NEGARA INDONESIA TAHUN 2006-2014 - Betzirita B11110061, Sri Sisca (Jurnal Manajemen Update, 2014)
This research aimed to test and analyze whether there is any influences of Loan To Deposit, Capital Adequacy, Non Performing Loan, and Net Profit Margin toward the distribution of credit in PT. Bank Negara Indonesia in period 2006-2014. The method used in this research was quantitative research. The object of this research was PT. in period 2006-2014. The data collecting technique were library study and documentation. The data analysis used in this research was regresi linier berganda. The finding indicated that Loan To deposit, and Capital adequancy had positive influence toward the distribution of credit but it was not significant. And Non performing Loan had negative influence toward the distribution of credit but it was not significant. The similar research of this research had the same findings. Whereas, Net Profit Margin had negative influence toward the distribution of credit but it was significant. The value of determination of coefisien (R2) was 0.514 or 51,4%, it meant the capability of the influences of all variables Loan To Deposit, Capital Adequancy, Non performing Loan, and Net Profit Margin toward the distribution of credit was quite enough 51,4%. Whereas the rest were influenced by another factor that was not be analyzed. Keywords : Loan To Deposit, Capital Adequancy, Non Performing Loan, Net Profit Margin and the distribution of credit.